Stable and mobile two-dimensional dipolar ring-dark-in-bright Bose-Einstein condensate soliton - Adhikari, S. K. [UNESP] (IOP Publishing, 2016)
We demonstrate robust, stable, mobile two-dimensional (2D) dipolar ring-dark-in-bright (RDB) Bose-Einstein condensate (BEC) solitons for repulsive contact interaction, subject to a harmonic trap along the y direction perpendicular to the polarisation direction z. Such a RDB soliton has a ring-shaped notch (zero in density) imprinted on a 2D bright soliton free to move in the x - z plane. At medium velocity the head-on collision of two such solitons is found to be quasi-elastic with practically no deformation. The possibility of creating the RDB soliton by phase imprinting is demonstrated. The findings are illustrated using numerical simulation employing realistic interaction parameters in a dipolar 164Dy BEC.
Keywords: BoseEinstein condensation; dipolar atoms; soliton